1998
DOI: 10.1523/jneurosci.18-10-03659.1998
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Cleavage of Caspase-3 in Apoptosis Induced by Experimental Cerebral Ischemia

Abstract: We examined the expression, activation, and cellular localization of caspase-3 (CPP32) using immunohistochemistry, immunoblots, and cleavage of the fluorogenic substrate N-benzyloxycarbonyl-Asp-Glu-Val-Asp-7-amino-4-trifluoromethyl coumarin (zDEVD-afc) in adult mouse brain after temporary (2 hr) middle cerebral artery occlusion produced by filament insertion into the carotid artery. Immunoreactive caspase-3p32 but not its cleavage product caspase-3p20 was constitutively expressed in neurons throughout brain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
510
3
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 843 publications
(555 citation statements)
references
References 50 publications
38
510
3
3
Order By: Relevance
“…Caspase 3 activation has been detected following focal (and global) ischaemic insults to the brain [14][15][16][17][18][19] where it coincides with areas of enhanced apoptotic cell death 14 and treatment with caspase 3 inhibitors has been reported to reduce infarct size following MCA occlusion. 14,[56][57][58] Moreover, studies in caspase 3-deficient mice indicate that these animals are relatively resistant to ischaemic insults with smaller lesions than their WT littermates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase 3 activation has been detected following focal (and global) ischaemic insults to the brain [14][15][16][17][18][19] where it coincides with areas of enhanced apoptotic cell death 14 and treatment with caspase 3 inhibitors has been reported to reduce infarct size following MCA occlusion. 14,[56][57][58] Moreover, studies in caspase 3-deficient mice indicate that these animals are relatively resistant to ischaemic insults with smaller lesions than their WT littermates.…”
Section: Discussionmentioning
confidence: 99%
“…10 The decreased apoptosis observed in the brain suggested a critical role for caspase 3 in the development of the central nervous system. Caspase 3 has also been implicated in cell death following a number of neurodegenerative insults including global ischaemia, 12,13 focal ischaemia, [14][15][16][17][18][19] transient ischaemia of the spinal cord, 20 neonatal cerebral hypoxia-ischaemia, [21][22][23] traumatic brain injury, [24][25][26] Alzheimer's disease, [27][28][29] Huntington's disease, [30][31][32] and Parkinson's disease. [33][34][35][36][37] It was therefore hypothesized that overexpression of caspase 3 may sensitize the animal to normal (physiological) apoptotic processes that occur during development and natural ageing and confer particular susceptibility to neurodegenerative insults.…”
Section: Introductionmentioning
confidence: 99%
“…In mature animals, Namura and colleagues showed that activated caspase-3 protein was detected within 12 h after stroke while peak caspase-3 activity was observed within 1 h [30]. In a similar model, Benchoua and colleagues demonstrated that caspase-8 activation occurs in the acute time periods after stroke while delayed cell death (after 24 h) occurs concurrently with activation of caspase-9, suggesting differential activation of the two caspase cascades [5].…”
Section: Caspases and Brain Injurymentioning
confidence: 99%
“…The timing of death varies among regions of the brain, from the early embryonic to the early postnatal periods. Mice lacking many of the other caspases, such as caspase 1, 2, 6, 11, or 12, do not have an obvious neuronal phenotype (Kuida et al, 1995;Bergeron et al, 1998;Namura et al, 1998;Wang et al, 1998;Zheng et al, 2000), but these caspases may play a role in regional pruning of neurons or in the plasticity of the nervous system.…”
Section: Developmental Death Pathways Inmentioning
confidence: 99%